Economic structure and sub-national policy in Argentina - Behrend, Jacqueline Mariela (2017)
This article aims to contribute to the debate on subnational state-society relations, focusing specifically on the Argentine case. To this end, we develop two specific objectives. First, we develop a theoretical and conceptual argument about the importance of studying the diversity of economic structures that exist at the subnational level, in order to understand the impact that they have on state-society relations. Second, we propose an analytic framework to classify the Argentine provinces according to their economic structure. This classification is based on three variables: the strength of the private sector in the provincial economy, the relative weight of the subnational state in the economy, and the type of production that predominates. On the basis of this classification, in the conclusions we hypothesize about the incentives that economic actors have to establish varying types of relations with the provincial state.